Psychological and Social Factors in Undergoing Reconstructive Surgery among Individuals with Craniofacial Conditions: An Exploratory Study. (March 2013) - Bemmels, Heather; Biesecker, Barbara; Schmidt, Johanna L.; Krokosky, Alyson; Guidotti, Rick; Sutton, Erica J.
Objective: Reconstructive surgery to improve psychological well-being is commonly offered to children with craniofacial conditions. Few studies have explored the challenges of reconstructive surgery beyond the physical risks: poor treatment outcomes, infection, brain damage, and death. This qualitative study aims to understand the psychological and social implications such interventions can have for individuals with craniofacial conditions. Design: A total of 38 individuals between the ages of 12 and 61 with such craniofacial conditions as Sturge-Weber syndrome, Treacher Collins syndrome, Möbius syndrome, cleft lip and palate, Noonan syndrome, Crouzon syndrome, and amniotic band syndrome participated in semistructured video-recorded interviews. Participants were recruited at conferences, through study flyers, and by word of mouth. Descriptive, thematic analysis was used to identify themes related to reconstructive surgery. Results: Dominant themes included undergoing surgery to reduce stigmatization, the psychological and social implications of the interventions, outcome satisfaction, parental involvement in decision making about surgery, and recommendations for parents considering surgery for their children with craniofacial conditions. Experiences with reconstructive surgery varied, with some participants expressing surgical benefits and others, disillusionment. Conclusions: The range of participant attitudes and experiences reflect the complexity of reconstructive surgery. Pediatric health care teams involved in the care of children with craniofacial conditions play an important role in advising patients (and their parents) about existing treatment options. The psychological and social implications of reconstructive surgery should be relayed to help families weigh the risks and benefits of surgery in an informed and meaningful way.